Why is Trichodesmium abundant in the Kuroshio? - T. Shiozaki; S. Takeda; S. Itoh; T. Kodama; X. Liu; F. Hashihama; K. Furuya (Biogeosciences, 2015)
The genus Trichodesmium is recognized as an abundant and major diazotroph in the Kuroshio, but the reason for this remains unclear. The present study investigated the abundance of Trichodesmium spp. and nitrogen fixation together with concentrations of dissolved iron and phosphate in the Kuroshio and its marginal seas. We performed the observations near the Miyako Islands, which form part of the Ryukyu Islands, situated along the Kuroshio, since our satellite analysis suggested that material transport could occur from the islands to the Kuroshio. Trichodesmium spp. bloomed (> 20 000 filaments L−1) near the Miyako Islands, abundance was high in the Kuroshio and the Kuroshio bifurcation region of the East China Sea, but was low in the Philippine Sea. The abundance of Trichodesmium spp. was significantly correlated with the total nitrogen fixation activity. The surface concentrations of dissolved iron (0.19–0.89 nM) and phosphate (< 3–36 nM) were similar for all of the study areas, indicating that the nutrient distribution could not explain the spatial differences in Trichodesmium spp. abundance and nitrogen fixation. Numerical particle-tracking experiments simulated the transportation of water around the Ryukyu Islands to the Kuroshio. Our results indicate that Trichodesmium growing around the Ryukyu Islands could be advected into the Kuroshio.